Digital bridges: new forms of communication, teaching and care in nursing (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
In this article we analyze how, since the COVID-19 pandemic, digital tools transformed nursing in Argentina. During the health emergency, online platforms became an essential means for continuing education, disseminating knowledge about care and connecting professionals. Along these lines, we examine the strategic use of social media, particularly the presence of female university graduates on Instagram, to promote health, counter misinformation, challenge stereotypes about the profession, and even monetize their services. We highlight that digital bridges of communication have expanded the territorial reach of nursing. By generating new dynamics of connection and outreach between universities and virtual communities, they have reconfigured the professional role beyond education and care settings.
Keywords: COVID-19 pandemic; nursing; digital communication; university outreach; professional role